Spatial Distribution and Casual Causes of Shallow Landslides in Jinbu Area of Korea - 박진우; 최병구; 김명환; 차두송 (Journal of forest and environmental science , 33(2), 2017)
In temperate monsoon regions, extensive shallow landslides triggered by heavy rainfall are recurrent phenomena in mountainous areas. 1,357 landslides over Jinbu area, Korea that totaled 127 km2 were identified from aerial photographs and field survey. We examined characteristics of rainfall-induced shallow landslides and casual factors affecting landslide distribution with respect to topographic and forest settings, and land use. Most landslides occurred in the study area were the results of a complex combination of precondition, preparatory factors and triggering factors. Cumulative rainfall and high intensity rainfall during short period of time made the study area very sensitive to landslides and played as catalysts to enable other factors including topographic and forest settings, and land use to act more effectively. In addition, some landslides at lower elevation involved channel incision or bank erosion influenced by land use changes such as deforestation and intensification of agriculture surrounding riparian forests or hillslopes. The results suggest that most of landslide were triggered by heavy rainstorms while topographic, forest settings, and land use affected landslide distribution occurred in the study area. KCI Citation Count: 1